2018
DOI: 10.1016/j.idcr.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Human Herpes Virus 6 and nivolumab-related pneumonitis: Potential pathogenetic insights

Abstract: The development of immune system modulating agents, such as immune checkpoint inhibitors (ICIs), has revolutionized cancer treatment. Nivolumab, a human monoclonal antibody against PD-1, has emerged as an efficient treatment for various malignancies, including non-small cell lung cancer (NSCLC); however, it is associated with important immune related side-effects, attributed to organ-specific inflammation, such as immune-mediated pneumonitis, a relatively uncommon, albeit potentially fatal adverse event. We he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…Our analysis (Table 2) showed that the overall recurrence ratios with and without re-challenge ICI therapy were 6.82% (3/44) and 22.73% (10/44), respectively. Among three patients (65,73,81) who re-challenged ICI therapy after clinical regression of CIP, two experienced recurrence after restarting ICIs (65,81), and one patient successfully improved by discontinuing immunotherapy and beginning treatment with antibiotics and steroids (73). Recurrent pneumonitis severity, location of involvement, and pattern might vary compared with the initial manifestation of CIP.…”
Section: Prognosis Of Cipmentioning
confidence: 98%
See 1 more Smart Citation
“…Our analysis (Table 2) showed that the overall recurrence ratios with and without re-challenge ICI therapy were 6.82% (3/44) and 22.73% (10/44), respectively. Among three patients (65,73,81) who re-challenged ICI therapy after clinical regression of CIP, two experienced recurrence after restarting ICIs (65,81), and one patient successfully improved by discontinuing immunotherapy and beginning treatment with antibiotics and steroids (73). Recurrent pneumonitis severity, location of involvement, and pattern might vary compared with the initial manifestation of CIP.…”
Section: Prognosis Of Cipmentioning
confidence: 98%
“…The interstitial inflammatory infiltration might include elevated levels of eosinophil, poorly formed granulomas, and lymphocytes (18). The cases that we included specifically mentioned the pathological manifestation of alveolar parenchyma with fibroblast foci (four cases) (73,78,79,85), mild collagen expansion of the alveolar septa (one case) (78), nonspecific chronic inflammation (four cases) (73,78,85), and atypical cells (one case) (79).…”
Section: Pathological Manifestationsmentioning
confidence: 99%
“…One case of Epstein-Barr (EBV)-induced acute cerebellar ataxia (confirmed with positive EBV DNA in the blood and CSF), and a case of fatal encephalitis, possibly in combination with concomitant pembrolizumab neurotoxicity have been reported [ 13 , 14 ]. Finally, a single case of biopsy-proven human herpes virus 6 pneumonitis [ 15 ] and 2 cases of pneumonia due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) strictly simulating ICI-induced pneumonitis have been reported [ 16–18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Activated fibroblasts and myofibroblasts can secrete ECM components, while myofibroblasts can produce contractile apparatus, such as α-smooth muscle actin microfilaments, which leads to the formation of fibroblastic foci and deposition of ECM ( 90 ). Fibroblastic foci in the alveolar parenchyma ( 91 93 ) and collagen expansion of the alveolar septa ( 94 ) have been detected in CIP lungs. These changes can destroy normal lung structures, causing a characteristic “honeycombing” morphology.…”
Section: Discussionmentioning
confidence: 99%